Preserving periodontium during cavity preparation - R. Amirlo (Tehran University of Medical Sciences, 1993)
In general, there is a direct relationship between dental restorations and periodontal condition of the mouth. During tooth preparation, it should be considered that gingival tissues (specially biologic width) must be preserved. Incorrect tooth preparation and therefore incomplete impression results in wrong contour of the final cast, plaque accumulation and gingivitis. Hence, Cervical anatomy of the teeth which determines final contour of the restoration is very important.  The amount of tooth tissue that should be removed relates to cervical contour of it before preparation. Over contoured restorations inhibit uscular movements and self cleasnsing mechanism. Shoulder finish line is preferred to knife edge due to the final convexity of tooth contour resulted from shoulder preparation.  In teeth with cingulum, preparation should be parallel to cervical third of buccal surface. This brings more retention. Final preparation and impression making should not be performed in the same visit.